Amphipathic Small Molecule AZT Compound Displays Potent Inhibitory Effects in Cancer Cell Proliferation - Pethaiah Gunasekaran; Ho Jin Han; Jung hoon Choi; Eun Kyoung Ryu; Nam Yeong Park; Geul Bang; Yeo Kyung La; Sunghyun Park; Kyubin Hwang; Hak Nam Kim; Mi-Hyun Kim; Young Ho Jeon; et al. (Pharmaceutics, 2021)
Cancer has been identified as a leading cause of death worldwide, and the increasing number of cancer cases threatens to shorten the average life expectancy of people. Recently, we reported a 3-azido-3-deoxythymidine (AZT)-based amphipathic small molecule, ADG-2e that revealed a notable potency against tumor metastasis. To evaluate the anticancer potential of ADG-2e, we assessed its anticancer potency in vitro and in vivo. Anticancer screening of ADG-2e against cervical cancer cells, HeLa CCL2, and BT549 mammary gland ductal carcinoma showed significant inhibition of cancer cell proliferation. Furthermore, mechanistic investigations revealed that cancer cell death presumably proceeded through an oncosis mechanistic pathway because ADG-2e treated cells showed severe damage on the plasma membrane, a loss of membrane integrity, and leakage of α-tubulin and β-actin. Finally, evaluation of the antitumorigenic potential of ADG-2e in mouse xenograft models revealed that this compound potentially inhibits cancer cell proliferation. Collectively, these findings suggest that ADG-2e can evolve as an anticancer agent, which may represent a model for nucleoside-based small molecule anticancer drug discovery.